Molecular mechanisms underlying plant memory in JA-mediated defence responses - Galis, Ivan; Gaquerel, Emmanuel; Pandey, Shree Prakash; Baldwin, Ian T. (Plant, cell & environment, 2008)
Plants must respond to biotic and abiotic challenges to optimize their Darwinian fitness in nature. Many of these challenges occur repeatedly during a plant's lifetime, and their sequence and timing can profoundly influence the fitness outcome of a plant's response. The ability to perceive, store and recall previous stressful events is likely useful for efficient, rapid and cost-effective responses, but we know very little about the mechanisms involved. Using jasmonate-elicited anti-herbivore defence responses as an example, we consider how ‘memories’ of previous attacks could be created in (1) the biosynthetic processes involved in the generation of the oxylipin bursts elicited by herbivore attacks; (2) the perception of oxylipins and their transduction into cellular events by transcription factors and transcriptional activators; and (3) the role of small RNAs in the formation of long-term stress imprints in plants.